Design Konseptual Model Pengelolaan Sampah di Kota Padang - Rahmayanti, Dina; Meuthia, Yumi; Aqila, Andini (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The increase in waste at the Padang City landfill (TPA) each year is caused by population growth and the imbalance between the amount of waste generated and the waste processing facilities at the source. As a result, inadequately processed waste at waste banks, TPS3R, and TPST ends up in the landfill, where space is increasingly limited. This study uses a Causal Loop Diagram (CLD) to identify and analyze the waste management and disposal system in Padang City and its impact on overall waste management. The conceptual model is created with three CLD submodels: the population submodel, the waste at source submodel, and the waste processing submodel. This study concludes that a more dynamic approach and comprehensive analysis of all aspects of waste management are needed to reduce waste accumulation at the landfill and increase its capacity in the future. The conceptual waste management model developed serves as an initial step in creating a dynamic system that can help solve waste problems effectively and sustainably.